Balloon angioplasty of severe aortic coarctation in a newborn, using axillary artery access: The first experience in Turkey - Kemal Nişli; Serra Karaca; Ümrah Aydoğan (KARE Publishing, 2016)
Axillary artery access for demanding interventions in newborns is rarely described, in spite of the many clear advantages. This access route in newborns with critical congenital heart disease is a real alternative to the more commonly used femoral or carotid artery routes. In brief, axillary access is an attractive alternative approach in newborns with complex heart diseases. It is advisable to stop an elective procedure if axillary access is not successful. Presently described is the use of axillary artery access for balloon angioplasty in a newborn with critical aortic coarctation. To the best of our knowledge, it was the first instance in Turkey.